Integrating RF Technologies for Robust Disaster Response and Recovery Systems - J.Salai Thillai Thilagam; Dr.M.V.R.Vittal; Dr.P.C.Praveen Kumar; Dr.D.V.Srihari Babu (International Journal of Radio Frequency Innovations, 2025)
In the aftermath of disasters, one of the greatest challenges is the failure of communication networks, which delays rescue operations and worsens human suffering. Radio Frequency (RF) technologies offer promising solutions as they enable wireless communication, sensing, and tracking without depending on fragile infrastructure. This paper presents a study of RF applications in disaster management and proposes a unique hybrid multi-layer framework that integrates environmental RF sensors, RFID-based tracking, drone-mounted RF relays, and satellite uplinks into one resilient system. Unlike existing standalone solutions, the proposed framework ensures redundancy, adaptability, and scalability across all phases of disaster management—preparedness, response, and recovery. The methodology describes how each layer functions step by step, creating a closed-loop system from sensing to decision-making. Expected outcomes include uninterrupted communication, improved victim localization, and faster coordination of relief efforts. Limitations such as interference and security challenges are addressed, along with future research directions combining RF with IoT, AI, and 5G networks for smarter disaster resilience.
Keywords: LoRa; RFID; Satellite communication; disaster management; hybrid framework; radio frequency; wireless sensor networks